Evaluating the Impact of Neurosurgical Rotation Experience in Africa on the Interest and Perception of Medical Students Towards a Career in Neurosurgery: A Continental, Multi-Centre, Cross-Sectional Study - Dada, Olaoluwa Ezekiel; Ooi, Setthasorn Zhi Yang; Bukenya, George William; Kenfack, Yves Jordan; Le, Chi; Ohonba, Efosa; Adeyemo, Emmanuel; Narain, Kapil; Awad, Ahmed K.; Barrie, Umaru; Sichimba, Dawin; Ogunfolaji, Oloruntoba; et al. (Frontiers in Surgery, 2022)
Objective Africa has the second highest neurosurgical workforce deficit globally and many medical students in Africa lack exposure to the field. This study aims to assess the impact of a neurosurgical rotation during medical school in shaping the perception and interest of students toward a career in neurosurgery. Study Design Cross-sectional study. Methods A Google form e-survey was disseminated to African clinical medical students between February 21st and March 20th, 2021. Data on exposure and length of neurosurgical rotation and perception of, and interest in, neurosurgery were collected. Data was analyzed using descriptive statistics and adjusted logistic regression modeling. Results Data was received from 539 students in 30 African countries (30/54, 55.6%). The majority of participants were male and were from Kenya, Nigeria and South Africa. Most students had undertaken a formal neurosurgery rotation, of which the majority reported a rotation length of 4 weeks or less. Students who had more than 4 weeks of neurosurgical exposure were more likely to express a career interest in neurosurgery than those without [odds ratio (OR) = 1.75, p < 0.04] and men were more likely to express interest in a neurosurgical career compared to women (OR = 3.22, p < 0.001), after adjusting for other factors. Conclusion Neurosurgical exposure is a key determinant in shaping the perception and interest of medical students toward a career in neurosurgery. Our findings support the need: i) for a continent-wide, standardized curriculum guide to neurosurgical rotations and ii) to advocate for gender inclusivity in education and policy-making efforts across the African continent.